Pregunta
upstudy study bank question image url

Evaluate: \[ \lim _{x \rightarrow-\infty} \frac{e^{-7 x}-2 e^{3 x}-e^{x}}{e^{-x}+16 e^{-10 x}+2 e^{-4 x}} \]

Ask by Pena Peterson. in Ghana
Feb 11,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The limit is 0.

Solución

¡Inicia sesión para desbloquear respuestas gratis!

Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.

star-icon Descubrir

Respondido por UpStudy AI y revisado por un tutor profesional

Mind Expander

To evaluate the limit \[ \lim _{x \rightarrow-\infty} \frac{e^{-7 x}-2 e^{3 x}-e^{x}}{e^{-x}+16 e^{-10 x}+2 e^{-4 x}}, \] we begin by analyzing the behavior of each term as \( x \to -\infty \). ### Numerator Analysis: 1. **Term \( e^{-7x} \)**: As \( x \to -\infty \), \( -7x \to +\infty \), so \( e^{-7x} \to +\infty \). 2. **Term \( -2e^{3x} \)**: As \( x \to -\infty \), \( e^{3x} \to 0 \), thus \( -2e^{3x} \to 0 \). 3. **Term \( -e^x \)**: Similarly, as \( x \to -\infty \), \( e^x \to 0 \), so \( -e^x \to 0 \). Thus, the dominant term in the numerator is \( e^{-7x} \to +\infty \). ### Denominator Analysis: 1. **Term \( e^{-x} \)**: As \( x \to -\infty \), \( -x \to +\infty \), hence \( e^{-x} \to +\infty \). 2. **Term \( 16e^{-10x} \)**: Here, \( -10x \to +\infty \), therefore \( e^{-10x} \to +\infty \) leading to \( 16e^{-10x} \to +\infty \). 3. **Term \( 2e^{-4x} \)**: Similarly, \( -4x \to +\infty \) implies \( e^{-4x} \to +\infty \), thus \( 2e^{-4x} \to +\infty \). Among these terms, we need to identify which grows the fastest as \( x \to -\infty \). Since exponential functions grow more quickly with increasing coefficients of their inputs, \( 16e^{-10x} \to +\infty \) grows fastest because of the highest coefficient of \( -10x \). ### Limit Calculation: Now, we rewrite the limit with the identified dominant terms. Both the numerator and denominator tend to \( +\infty \). We can simplify by factoring out the dominating exponentials: 1. In the **numerator**, factor out \( e^{-7x} \): \[ e^{-7x}(1 - 2 e^{10x} - e^{-6x}). \] Here, as \( x \to -\infty \), \( e^{10x} \to 0 \) and \( e^{-6x} \to +\infty\). We still have the overall behavior dominated by \( e^{-7x} \). 2. In the **denominator**, factor out \( e^{-10x} \): \[ e^{-10x}(16 + 2 e^{6x} + e^{4x}). \] Again, as \( x \to -\infty \), the term \( e^{6x} \) and \( e^{4x} \) tend towards 0. Now substituting back into the limit gives us: \[ \lim_{x \to -\infty} \frac{e^{-7x}(1 - 2e^{10x} - e^{-6x})}{e^{-10x}(16 + 2e^{6x} + e^{4x})} = \lim_{x \to -\infty} \frac{e^{3x}(1 - 2e^{10x} - e^{-6x})}{16 + 2e^{6x} + e^{4x}}. \] As \( x \to -\infty\), \( e^{3x} \to 0\). Therefore, both \( 1 - 2e^{10x} \to 1 \) and \( 16 + 2e^{6x} + e^{4x} \to 16\), leading to: \[ = \frac{0}{16} = 0. \] Finally, the limit is \[ \boxed{0}. \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad